2020
DOI: 10.3390/jrfm13040062
|View full text |Cite
|
Sign up to set email alerts
|

Board-Gender Diversity, Family Ownership, and Dividend Announcement: Evidence from Asian Emerging Economies

Abstract: In eras of intense debates on the appointment of women on corporate boards, this research sheds light on the structure of board in Asian emerging economies by examining how women on board of family businesses separately and collectively affect the dividend announcement of business organizations. On the basis of the panel data of four Asian emerging economies—China, Malaysia, Pakistan, and India—for the period 2010–2018, the results from our Tobit regression showed the adverse (negative) and significant impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 120 publications
1
29
0
1
Order By: Relevance
“…Trinh et al (2020) also demonstrated a positive relationship between gender diversity and dividend payments. Finally, McGuinness et al (2015) provided positive but insignificant results in this context, while Mustafa et al (2020) showed negative relationship between gender diversity and dividend announcements.…”
Section: Board Gender Diversity and Dividend Payoutsmentioning
confidence: 81%
See 1 more Smart Citation
“…Trinh et al (2020) also demonstrated a positive relationship between gender diversity and dividend payments. Finally, McGuinness et al (2015) provided positive but insignificant results in this context, while Mustafa et al (2020) showed negative relationship between gender diversity and dividend announcements.…”
Section: Board Gender Diversity and Dividend Payoutsmentioning
confidence: 81%
“…Finally, McGuinness et al (2015) provided positive but insignificant results in this context, whileMustafa et al (2020) showed negative relationship between gender diversity and dividend announcements.…”
mentioning
confidence: 85%
“…Women’s directors improve monitoring, mitigate agency conflicts and enhance dividend payouts (Adams and Ferreira, 2009; Byoun et al , 2016; Pucheta-Martínez and Bel-Oms, 2016; Chen et al , 2017; Ye et al , 2019; Ahmed et al , 2020; Mustafa et al , 2020; Ain et al , 2021; Thompson and Manu, 2021). Female directors are also competent and hardworking, with a better record of attending meetings than their male counterparts (Adams and Ferreira, 2009).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…On the contrary, few researchers determine adverse influence of board gender diversity with organizational performance (Mukarram et al, 2018;Sani, 2021;Suciu et al, 2021;Vo & Bui, 2017). Mustafa et al, (2020) concluded that board gender diversity negatively influence firm divident payout that is eventually reflected in the market capitalization of the firm. Aghadike, (2021) found that in Nigeria corporate board diversity dampens the financial performance.…”
Section: Literature Review 21 Board Gender Diversity and Firm Performancementioning
confidence: 99%